2015
DOI: 10.1111/plb.12351
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth‐promoting effects of native Pseudomonas strains on Mentha piperita (peppermint): an in vitro study

Abstract: Plant growth-promoting rhizobacteria (PGPR) affect growth of host plants through various direct and indirect mechanisms. Three native PGPR (Pseudomonas putida) strains isolated from rhizospheric soil of a Mentha piperita (peppermint) crop field near Córdoba, Argentina, were characterised and screened in vitro for plant growth-promoting characteristics, such as indole-3-acetic acid (IAA) production, phosphate solubilisation and siderophore production, effects of direct inoculation on plant growth parameters (sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 59 publications
3
31
0
3
Order By: Relevance
“…However, longer roots and higher dry weight of roots was only evidenced in the soybean plants from the ISIB55-PVA and ISIB55-treated seeds (Fig 5B, 5C and 5D). It has been reported that native isolates are previously adapted to the local environment, which results in a competitive advantage over non-natives strains [70]. Thus, the present results suggest that P .…”
Section: Discussionsupporting
confidence: 65%
“…However, longer roots and higher dry weight of roots was only evidenced in the soybean plants from the ISIB55-PVA and ISIB55-treated seeds (Fig 5B, 5C and 5D). It has been reported that native isolates are previously adapted to the local environment, which results in a competitive advantage over non-natives strains [70]. Thus, the present results suggest that P .…”
Section: Discussionsupporting
confidence: 65%
“…In the present study the enhanced number of glandular trichomes in bioinoculant treatments in comparison with the control suggested the possible role of bioinoculants in stimulating the production of plant hormones. The greater number of glands may further be related to alterations in the principal aroma profile of the plants …”
Section: Resultsmentioning
confidence: 99%
“…The greater number of glands may further be related to alterations in the principal aroma profile of the plants. 26…”
Section: Effect Of Bioinoculants On Biomass Secondary Metabolites Anmentioning
confidence: 99%
“…Pseudomonas spp. beneficial effects on plant growth promotion have been associated with various mechanisms, including the production of antibiotics, the stimulation of plant defence systems through induced systemic resistance, the enhancement of plant nutrient uptake, the secretion of vitamins and siderophores, the synthesis of phytohormones and the production of 1‐aminocyclopropane‐1‐carboxylate (ACC) deaminase which degrades the ethylene precursor ACC (Parejko et al ; Ali et al ; Santoro et al ). Regardless of the mechanism(s) involved, the plant growth promotion effect due to Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Significance and Impact of the Study: LBUM677 shows great potential to be used as an inoculum to promote oil yield and fatty acid accumulation in oilseed crops. Ali et al 2014;Santoro et al 2015). Regardless of the mechanism(s) involved, the plant growth promotion effect due to Pseudomonas spp.…”
mentioning
confidence: 99%